Undergraduate Experiences in Extension-Based Programming Education for Public School Students - Souza, Maria Eduarda T.; Silva, João Pedro R.; Silva, Matheus E. Da; Maia, Eduardo H. B.; Silva, Alisson Marques Da; Silva, André L. M.; Araújo, Thabatta M. A. De (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
This study explores the impact of an outreach initiative on undergraduate Computer Engineering students at CEFET-MG campus, Divinopolis, who taught programming and robotics in local public schools. Adopting a participant research methodology, the study collected data through structured surveys and interviews conducted between 2023 and 2024. Findings reveal that the project significantly developed essential competencies in the undergraduate students, such as communication, teamwork, and problem-solving. It also had a positive impact on the partner schools by enhancing students' logical thinking and increasing their interest in digital technologies. However, the study also identified key challenges, including limited resources, logistical difficulties, and the need for additional pedagogical training for the student instructors. The paper concludes by emphasizing the need for structured logistical support, didactic preparation, and institutional partnerships to maximize the potential of such projects. It recommends that future studies incorporate longitu-dinal analyses and the perspectives of public school students to gain a more complete understanding of the project's long-term effects.